A home-made hybrid system for the simultaneous determination of ergotamine, dipyrone and caffeine in pharmaceutical preparations - Di Nezio, Maria Susana (2007)
A novel home-made hybrid detection system was designed for simultaneous determination of caffeine (CAF), dipyrone (DIP) and ergotamine (ERG) in pharmaceutical preparations. Thus, ERG was determined by a fluorimetric signal and PLS-1 method for resolving DIP and CAF UV-V spectral data was used. The calibration curve for ERG was linear over the range 2.5 - 10 mg L-1. The calibration set consisted of 18 mixtures with 0.5 to 4 mg L-1 for CAF, 5 to 20 mg L-1 for DIP and 2.5 and 10 mg L-1 for ERG. Sample preparation prior to analysis was not required. A recovery study with the real samples was carried out and the obtained results were highly satisfactory.